Intra-artery infusion of recombinant human erythropoietin reduces blood–brain barrier disruption in rats following cerebral ischemia and reperfusion. (2nd September 2015) - Wang, Rongliang; Wu, Xiaoning; Liang, Jia; Qi, Zhifeng; Liu, Xiangrong; Min, Lianqiu; Ji, Xunming; Luo, Yumin; Zhao, Haiping
<x xml:space="preserve">Abstract</x> Objectives: Intra-artery infusion of recombinant human erythropoietin (rhEPO) has recently been reported to confer neuroprotection against cerebral ischemia-reperfusion injury in animal models; however, the molecular mechanisms are still under investigation. The present study focused on the specific mechanism involved in blood–brain barrier (BBB) disruption. Methods: Thirty-six male and nine female Sprague Dawley rats were subjected to middle cerebral artery (MCA) occlusion to induce focal cerebral ischemia, and administrated rhEPO at a dose of 800 U/kg through MCA infusion at the beginning of reperfusion. Neurobehavioral deficits, brain edema, and infarct volume were evaluated after 2 h of ischemia and 24 h of reperfusion. BBB permeability was assessed by quantifying the extravasation of Evans blue (EB) dye. The expression of tight junction proteins and matrix metalloproteinases (MMPs) (Claudin-5, Occludin, MMP-2, and MMP-9) in microvessels were detected by immunofluorescence and western blot. The activities of MMPs in the cerebral microvessels were determined by gelatin zymography. Results: Treatment with rhEPO through the MCA strongly alleviated infarct volume, brain edema, and improved neurobehavioral outcomes in male and female rats. In addition, rhEPO remarkably suppressed the EB extravasation induced by brain ischemia. Furthermore, rhEPO prevented degradation of Claudin-5 and Occludin, and reduced the expression and activity of MMP-2 and MMP-9 in isolated brain microvessels. Conclusions: Treatment with rhEPO through MCA infusion prevented brain edema formation and infarction through inhibition of MMP-mediated BBB disruption in acute ischemic stroke.